Inclusão da camomila no desempenho, comportamento e estresse em codornas durante a fase de recria - Marques, Rafael Henrique [UNESP] (2010)
The objective of this study was to test the effect of Matricaria chamomila on the stress of the Japanese quails in the rearing period. In the rearing phase, from 28 to 42 days old, 192 quails were lodged to cages and allotted to completely randomized blocks design, with four diets (0; 250; 500 and 750mg of chamomile/kg of ration), with eight replicates and six birds per cage. Performance (feed intake, body weight gain, and feed conversion ratio), behavior (body injury, tonic immobility and focal observation) and physiological parameters (corticosterone plasmatic and heterophil/lymphocyte ratio) were evaluated. The tested chamomile levels did not affect performance, behavior and physiological parameters of quails in the rearing phase.